2013
DOI: 10.5888/pcd10.130052
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Welfare of Rural and Urban Cancer Survivors in Missouri

Abstract: IntroductionAn estimated 2.8 million cancer survivors reside in rural areas in the United States. We compared the risk behaviors, psychosocial factors, health outcomes, quality of life, and follow-up care of rural and urban cancer survivors in Missouri.MethodsWe used 2009–2010 Missouri Behavioral Risk Factor Surveillance System data to examine various health outcomes, behaviors, and psychosocial factors among rural and urban cancer survivors and their respective rural and urban counterparts without a cancer hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Schootman et al (2013) conducted the only statistical tests of determinants of SCP receipt in their study of Missouri cancer survivors, 24% of survivors received SCP; rural survivors were less likely than urban survivors to receive a SCP. 41 Some of the studies identified the nurse as the person who delivered the SCP. 15, 21, 31, 31 However most inferred that the oncologist was responsible for delivering the SCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schootman et al (2013) conducted the only statistical tests of determinants of SCP receipt in their study of Missouri cancer survivors, 24% of survivors received SCP; rural survivors were less likely than urban survivors to receive a SCP. 41 Some of the studies identified the nurse as the person who delivered the SCP. 15, 21, 31, 31 However most inferred that the oncologist was responsible for delivering the SCP.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes of interest included SCP use in cancer programs and among cancer care providers (6 of 14 studies); survivor and PCP receipt of SCP (5 of 14 studies); retention of SCP (1 of 14 studies); and determinants of SCP use (7 of 14 studies). 26,[29][30][31][32][33][34][35][36][37][38][39] All of these studies are summarized in Table 3. To measure these outcomes, most SCP dissemination and implementation studies used surveys (11 of 14 studies); 2 used interviews; and 1 used both interviews and focus groups.…”
Section: Dissemination and Implementationmentioning
confidence: 99%
“…Out-of-pocket costs and burden among rural breast cancer survivors Maria Pisu 1,2 , Andres Azuero 2,3 , Rachel Benz 3 , Patrick McNees 2,4,5 & Karen Meneses 2,3 report worse physical and mental health as well as being more likely to be unemployed due to health reasons than their urban counterparts [14][15][16]. They also face several challenges in accessing care due to scarce medical resources and the need to travel longer distances to visit doctors and receive care [17][18][19].…”
Section: Original Researchmentioning
confidence: 99%
“…The population of rural cancer survivors deserves some attention with regard to the OOP costs they may incur and the burden that these may cause. Rural cancer survivors report worse physical and mental health as well as being more likely to be unemployed due to health reasons than their urban counterparts . They also face several challenges in accessing care due to scarce medical resources and the need to travel longer distances to visit doctors and receive care .…”
Section: Introductionmentioning
confidence: 99%
“…Both quantitative and qualitative measurements indicated that the concept of rurality was a risk factor for low mental health, low quality of life, low physical wellbeing, poor self-rated health, higher level of distress, smoking and lower level of physical activities 3,4,8,9,11,14,22,23 . A summary of the key variables/ measurements for both quantitative and qualitative studies is provided in Tables 1 and 2.…”
Section: Descriptive Findings and Measurement Tools For Assessing Carmentioning
confidence: 99%